SYNTHESIS AND STUDY OF BIOLOGICAL ACTIVITIES OF2,6-DIARYLPIPERIDONE –y-DERIVATIVES - Hamak, Kh.; Kandil, F.; Hamo, S. (Iraqi Journal of Science, 2024)
In the present study new series of2,6-diarylpiperidones-4 derivative were synthesized and these compounds are :1-(1-oxo-2-chloro-ethyl)-3,3-dimethyl-2.6-diarylpiperidone-4(I)1-(1-oxo-2-chloro-ethyl)-3.5-dimethyl-2,6-diarylpiperidone-4(II)1-(1-oxo-2-imidazolyl-ethyl) -3,3-dimethyl-2,6-diphenyl piperidoe-4(III)1-(1-oxo-2-imidazolyl-ethyl)-3,5-dimethyl-2,6-diphenylpiperidoe-4 (IV)The prepared compounds were characterized by IR,LC-MS and 1H,13C-NMR spectra .All compounds were screened for their antibacterial activity against gram positive bacteria :Bacillus subtilis and gram negative bacteria :Escherichia coli at different concentration (1000, 500, 250, 100) ppm. These compounds show good activity against gram positive more than gram negative bacteria